Pengaruh Promosi dan Saluran Distribusi Terhadap Brand Awareness dan Dampaknya Pada Minat Beli Kaos Kaki Champ - Sri Marini (ATRABIS: Jurnal Administrasi Bisnis (e-Journal), 2019)
This study aims to obtain empirical evidence about the effect of promotion and channel distribution to the impact on brand awareness and purchase intentions socks champ . The results are expected to contribute in the development of marketing management , especially management . For those of similar companies and practitioners expected results of this study can provide useful information about the importance of the promotion , distribution channels and brand awareness in an effort to increase interest in purchasing . The study was conducted at 5 Borma department store branches in Bandung city . The method of research using survey methods with quantitative research approaches . While the type of research in the form of Descriptive Research and Research Explanation Verificative the time horizon in the form of cross - sectional data that reflects the picture of a state at a given moment . To test the hypothesis of statistical methods of research used path analysis. Test results of research found a significant relationship between promotion and distribution channels to brand awareness either simultaneously or partially . It was also found significant relationship between promotion , distribution channels and brand awareness to purchase intentions either simultaneously or partially.